LEGAL REGULATION OF AGRICULTURAL LABOUR IN INDIA: A CRITICAL STUDY - Dr. K. CHINNAM NAIDU (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Indian Planners have committed themselves to improve the conditions of Agricultural Labour. It has been the endeavor of every Five Year Plan in India to ensure fuller opportunities for work and better living to all the sections of the rural community and, in particular, to assist agricultural labourers and backward classes to come to the level of the rest. Even though there has been tremendous progress in India since Independence, the Government of India gave special consideration to the landless agricultural labour, this is one section which has really a very hard time and which deserves very special consideration. Still seasonal unemployment is a characteristic feature of Agricultural sector and under employment of man power is inherent in the system of family farming. Unlike industrial labour, agricultural labour is difficult to define. The reason is that unless capitalism develops fully in agriculture, a separate class of workers depending wholly on wages does not come up.